Transition metal oxide composite lithium oxalate lithium supplementing agent, and preparation method and application thereof
Patent Information
- Application Number
- CN202610739441.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-27
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]本发明针对现有草酸锂补锂体系中分解电位高、催化效率低、复合工艺复杂且产业化适配性差的技术问题,提供一种过渡金属氧化物复合草酸锂补锂剂及其制备方法和应用,采用干式球磨复合工艺,将过渡金属氧化物与导电碳材料一步嵌入草酸锂基体,使其在草酸锂基体表面相互交织形成连续导电网络,构建稳定的“催化相-锂源相-导电相”三相协同结构,最终实现草酸锂分解电位的有效降低,同时达成补锂剂催化活性与界面稳定性的双重提升
1、催化活性突破性提升:通过过渡金属氧化物与草酸锂构建原位催化界面,结合碳材料的高导电通路,将草酸锂分解电位从4.5V降至3.7~3.9V(<4.0V);电池首次充电效率也提升至91.5~94.5%。
Smart Images

Figure CN122889751A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery technology, specifically relating to a transition metal oxide composite lithium oxalate lithium supplement agent, its preparation method, and its application. Background Technology
[0002] Lithium oxalate (Li₂C₂O₄), as a lithium source compensation material for lithium-ion batteries, possesses outstanding advantages such as high theoretical specific capacity (525 mAh / g), environmental friendliness, and good thermal stability. It can decompose and release Li⁺ during the first charge of the battery, effectively compensating for irreversible lithium loss caused by the formation of the SEI film on the negative electrode, thereby improving the coulombic efficiency and capacity retention rate of the battery in the first cycle. This has made it an important research direction for lithium battery lithium replenishment materials. However, lithium oxalate has inherent drawbacks; its oxidation decomposition potential is as high as 4.5V (vs. Li₂C₂O₄). + The voltage is above 4.3V ( / Li), which significantly exceeds the stability window of commercial electrolytes (<4.3V). This can easily trigger electrolyte oxidation side reactions, reduce battery cycle life, and pose safety risks.
[0003] To lower the decomposition potential of lithium oxalate, researchers have attempted to combine catalysts such as metal oxides and metal phosphides with lithium oxalate. Among them, composite lithium supplementers, represented by Co3O4 / lithium oxalate, can reduce the decomposition potential to 4.2V, but their catalytic efficiency is limited, requiring an addition ratio of more than 10% to achieve improved lithium supplementation performance. Meanwhile, traditional composite processes often employ solvothermal methods, which suffer from drawbacks such as cumbersome steps, high energy consumption (>5kWh / kg), residual organic solvents, and poor batch stability, making it difficult to meet the demands of large-scale industrial applications. Summary of the Invention
[0004] This invention addresses the technical problems of high decomposition potential, low catalytic efficiency, complex composite processes, and poor industrial applicability in existing lithium oxalate supplementation systems. It provides a transition metal oxide composite lithium oxalate supplementer, its preparation method, and its application. The invention employs a dry ball milling composite process to embed transition metal oxides and conductive carbon materials into a lithium oxalate matrix in one step. This allows them to interweave on the surface of the lithium oxalate matrix to form a continuous conductive network, constructing a stable three-phase synergistic structure of "catalytic phase-lithium source phase-conductive phase". Ultimately, this effectively reduces the decomposition potential of lithium oxalate while simultaneously improving the catalytic activity and interfacial stability of the supplementer.
[0005] To address the aforementioned technical problems, this invention provides a method for preparing a transition metal oxide composite lithium oxalate lithium supplement, comprising the following steps: S1. Material Mixing: Transition metal oxides, highly conductive carbon materials, and lithium oxalate are mixed in a mass ratio of (1.5–2.5):(0.8–1.5):(12–15) to obtain a mixture; the transition metal oxide is at least one of Mn3O4, Fe3O4, and Co3O4; the highly conductive carbon material is at least one of carbon nanotubes, few-layer graphene, and conductive carbon black. S2. Dry ball milling composite: The mixture is placed in a high-energy ball mill, with zirconium oxide or tungsten carbide as the ball milling medium. Under an inert atmosphere, the ball-to-material ratio is set to 10:1 to 20:1, the rotation speed is 400 to 500 rpm, the ball milling time is 2 to 3 hours, and the energy input is 1.0 to 1.5 kWh / kg for dry ball milling composite. This allows the transition metal oxides and highly conductive carbon materials to be uniformly dispersed and embedded in the lithium oxalate matrix to form an electronic coupling interface. S3. Post-processing: After the ball-milled product is passed through a 200-300 mesh sieve, the composite powder is collected and vacuum dried to obtain the transition metal oxide composite lithium oxalate supplement.
[0006] This invention achieves precise control over the ratio of transition metal oxides and highly conductive carbon materials, as well as the ball milling energy input: When the proportion of transition metal oxides is <1.5%, the interfacial catalytic capacity is insufficient, and the decomposition initiation voltage of lithium oxalate is higher than 4.0V; when the proportion is >2.5%, the proportion of inert components is too high, resulting in a low overall specific capacity of the lithium replenishment agent. When the proportion of highly conductive carbon materials is <0.8%, the interfacial electronic conduction pathway is insufficient, leading to high interfacial impedance; when the proportion is >1.5%, insufficient structural toughness results in pulverization and detachment, and a decrease in electrode compaction density. When the ball milling energy input is <1.0kWh / kg, the interfacial coupling between the metal oxides and lithium oxalate is insufficient; when the energy is >1.5kWh / kg, the lithium oxalate crystal structure is distorted, affecting the stability of the lithium replenishment reaction. Based on this, the preparation method provided by this invention is simple and efficient. It completes the composite process in one step by dry ball milling, realizing the uniform dispersion and strong electronic coupling of transition metal oxides and conductive carbon materials on lithium oxalate matrix. The entire process is solvent-free, reducing energy consumption by more than 70% and shortening the production cycle by 60% compared with traditional wet processes. The finished product can be obtained by simple sieving and drying after ball milling. It is compatible with industrial-grade equipment such as planetary ball mills. The raw materials are all commercially available common types, requiring no complex pretreatment. It has the advantages of being green and environmentally friendly, cost-controllable, and having high batch stability, making it highly adaptable to industrialization.
[0007] As a further description of the above technical solution: the transition metal oxide in step S1 has a particle size of 50–150 nm; the lithium oxalate has a purity ≥99.5% and a particle size of 3–8 μm. This limitation on particle size and purity is a key matching design for achieving a three-phase synergistic structure. The 50–150 nm transition metal oxide possesses a large specific surface area to provide sufficient catalytic active sites, while avoiding agglomeration problems caused by excessive fineness. It can also be precisely embedded in the gaps between lithium oxalate particles and in the microcracks and pores on the surface. The 3–8 μm high-purity lithium oxalate, as a lithium source matrix, ensures the overall specific capacity of the lithium source supply and the lithium replenishment agent, avoiding electrochemical side reactions introduced by impurities. Simultaneously, this particle size gradient matching is suitable for dry ball milling processes, enabling efficient and uniform composite formation of the oxide and lithium oxalate under conventional ball milling parameters. This strengthens the two-phase electronic coupling effect, allowing the oxide and conductive carbon materials to better interweave on the lithium oxalate surface to form a continuous conductive network, reducing interfacial charge transfer impedance and improving electrochemical kinetic performance.
[0008] As a further description of the above technical solution: the conductive carbon black in step S1 is preferably SuperP or Ketjenblack EC-600JD, which combines high specific surface area, excellent electronic conductivity and structural dispersion, and can efficiently interweave with nanoscale transition metal oxides to rapidly construct a continuous and dense conductive network on the surface of the lithium oxalate matrix, significantly reducing the interfacial charge transfer impedance and accelerating the Li... + It facilitates insertion / extraction and electron transport; it is also compatible with dry ball milling processes, has good compatibility with transition metal oxides and lithium oxalate, does not cause powder agglomeration, and can enhance the binding of lithium supplementation agents with other components of electrode slurry, improve the stability of electrode structure, and provide reliable conductive support for the electrochemical performance of the three-phase synergistic structure.
[0009] As a further description of the above technical solution: the inert atmosphere in step S2 is argon or nitrogen, and the oxygen concentration in the inert atmosphere is <1ppm. This can effectively prevent the oxidation of transition metal oxides and the side reaction between lithium oxalate and oxygen during ball milling, which would lead to the loss of active lithium. At the same time, it can prevent the powder from agglomerating due to oxidation and the decrease in interfacial coupling effect, thus ensuring the catalytic activity of transition metal oxides and the lithium source purity of lithium oxalate. This ensures that a stable catalyst-lithium source interface and a continuous three-phase synergistic structure can be formed after ball milling, maintaining the excellent electrochemical performance of the lithium replenishing agent.
[0010] As a further description of the above technical solution: Before the dry ball milling compounding in step S2, 0.5 wt% of a surfactant, namely PVP or SDS, is added to the mixture. Adding a surfactant to the mixture can effectively reduce the surface energy between powder particles, preventing the agglomeration of transition metal oxide nanoparticles before and during ball milling, ensuring uniform dispersion of the catalytic phase on the lithium oxalate matrix surface. Simultaneously, it can improve the wettability and binding properties between materials, facilitating better embedding of transition metal oxides and conductive carbon materials into the lithium oxalate matrix during dry ball milling and the formation of a continuous conductive network. This further strengthens the interfacial coupling effect of the catalytic phase-lithium source phase-conductive phase, ensuring the uniformity and stability of the three-phase synergistic structure, and fully leveraging the catalytic activity and electrochemical performance of the lithium supplement.
[0011] As a further description of the above technical solution: the dry ball milling process in step S2 employs a jacketed water-cooled ball mill jar or a pulse operation strategy (e.g., running for 10 minutes, then pausing for 5 minutes) to control the ball milling temperature at <50℃. This effectively avoids the problem of excessively high local temperatures caused by mechanical friction heat generation during ball milling, and prevents lithium oxalate from prematurely decomposing and releasing Li due to high temperatures. + This process avoids the loss of active lithium while preventing transition metal oxides from undergoing crystal transformation and catalytic activity reduction due to high temperatures. It ensures the structural and performance integrity of each raw material, guarantees the formation of a stable three-phase synergistic structure after dry ball milling, maintains the lithium release efficiency and catalytic activity of the lithium supplement, and avoids problems such as powder agglomeration and deterioration of interface coupling caused by high temperatures, thereby improving the performance consistency of the lithium supplement product.
[0012] This invention also provides a transition metal oxide composite lithium oxalate supplement prepared by the above-described method. The transition metal oxides are uniformly dispersed at the nanoscale and embedded in the microcracks and pores on the surface of the lithium oxalate particles, forming an electronic coupling with the lithium oxalate. Simultaneously, the transition metal oxides and highly conductive carbon materials intertwine on the surface of the lithium oxalate matrix, forming a dense and continuous conductive network, thereby constructing a stable and continuous three-phase synergistic structure of "catalytic phase-lithium source phase-conductive phase". This lithium supplement can release Li in situ during the first charge of the battery. + This effectively reduces the decomposition potential of lithium oxalate to below 4.0V, thereby increasing the battery's coulombic efficiency to over 91% in the first week.
[0013] This invention also provides the application of the aforementioned transition metal oxide composite lithium oxalate lithium replenisher as a positive electrode additive in the preparation of lithium-ion battery positive electrode sheets, which can effectively compensate for the irreversible lithium loss caused by the formation of the SEI film in the negative electrode. Relying on the dual advantages of catalysis and conductivity of the synergistic three-phase structure of "catalytic phase-lithium source phase-conductive phase," this invention reduces the lithium oxalate decomposition potential from above 4.5V to 3.74–3.82V, which is highly matched with the stability window of commercial electrolytes, increasing the battery's first-cycle coulombic efficiency to over 91.5%, with an optimal level reaching 94.5%.
[0014] As a further description of the above technical solution: the amount of the transition metal oxide composite lithium oxalate supplement agent added to the positive electrode of the lithium-ion battery is 8-12% of the mass of the positive electrode active material. If the addition ratio is less than 8%, the coulombic efficiency improvement in the first cycle is less than 5%, and the lithium supplementation effect is limited; if the addition ratio is higher than 12%, the electrode thickness expansion rate exceeds 15% after 100 cycles, which will significantly degrade the electrode structure stability and energy density matching. Using the optimal addition range of 8-12%, the best balance between lithium source compensation and catalytic effect can be achieved without diluting the effective capacity of the positive electrode or significantly increasing the electrode thickness and interface impedance, avoiding problems such as side reactions, gas generation and electrode expansion caused by improper addition. This lithium supplement agent has good compatibility with existing lithium battery production processes such as positive electrode slurry preparation and coating. After 100 charge-discharge cycles, the electrode structure integrity retention rate is >98%, and the capacity decay rate is <0.15% / week, which can significantly improve the initial electrochemical performance and long-term cycle stability of lithium-ion batteries.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. Breakthrough improvement in catalytic activity: By constructing an in-situ catalytic interface between transition metal oxides and lithium oxalate, and combining it with the highly conductive pathway of carbon materials, the decomposition potential of lithium oxalate is reduced from 4.5V to 3.7-3.9V (<4.0V); the first charge efficiency of the battery is also improved to 91.5-94.5%.
[0016] 2. Significantly enhanced interface and structural stability: The dual structure of "nanocatalytic particle embedding-carbon network coating" constructed by high-energy ball milling greatly improves the structural retention rate of active materials during cycling; after 100 cycles of charge and discharge, the electrode surface has no obvious pulverization or interface delamination, the structural integrity retention rate is >98%, and the capacity decay rate is <0.15% / week, effectively alleviating the problem of rapid capacity decay caused by the instability of traditional lithium oxalate replenishment system.
[0017] 3. Significantly optimized preparation process cost: The solvent-free dry high-energy ball milling composite process eliminates the need for solvent heat treatment, washing, freeze drying, and other steps, with overall energy consumption controlled at 1.0-1.5 kWh / kg, which is more than 70% lower than the energy consumption of traditional wet composite processes; the production cycle is shortened by 60%, and the pollution and residue problems of organic solvents are completely avoided, meeting the industrial development requirements of green manufacturing.
[0018] 4. Strong industrial adaptability: The preparation of lithium supplement is compatible with commercial lithium oxalate (purity ≥99.5%) and other raw materials. The ball milling process is compatible with industrial-grade equipment such as planetary ball mills and vibratory mills. The composite powder can be directly added to the positive electrode slurry system. The slurry has good dispersibility and high stability. There is no need to adjust the existing electrode homogenization, coating and rolling processes. It can be directly connected to the existing production process of the lithium battery industry. Attached Figure Description
[0019] Figure 1 This is a SEM image of lithium oxalate.
[0020] Figure 2 This is a SEM image of the Co3O4 / carbon nanotube composite lithium oxalate supplement in Example 1.
[0021] Figure 3 XPS spectrum of the Co3O4 / conductive carbon black composite lithium oxalate supplement in Example 2.
[0022] Figure 4 This is a SEM image of the Mn3O4 / carbon nanotube composite lithium oxalate supplement in Example 4.
[0023] Figure 5 SEM image of Co3O4 / carbon nanotube composite lithium oxalate prepared by wet process in Comparative Example 1. Detailed Implementation
[0024] The present invention will be further described in detail below with reference to specific embodiments. The scope of protection of the present invention is not limited to the following embodiments, and all equivalent transformations based on the technical solutions of the present invention fall within the scope of protection of the present invention.
[0025] All raw materials used in this embodiment are commercially available conventional raw materials. The particle size of the transition metal oxides is controlled between 50 and 150 nm, the lithium oxalate has a purity of ≥99.5% and a particle size of 3 to 8 μm, the highly conductive carbon material is a commercially available conventional product, and the binder PVDF and conductive agent SuperP are commonly used auxiliary materials in the lithium battery industry.
[0026] Example 1: Co3O4 / carbon nanotube composite lithium oxalate supplement This embodiment provides a Co3O4 / carbon nanotube composite lithium oxalate supplement, which is composed of a lithium oxalate matrix (commercially available, purity ≥99.5%, D50=5μm), Co3O4 (commercially available, particle size 90nm), and carbon nanotubes (CNTs, diameter 20nm, length 1-5μm). Co3O4 is uniformly dispersed at the nanoscale and embedded in the microcracks and pores on the surface of lithium oxalate particles, forming an electronic coupling with lithium oxalate. At the same time, Co3O4 and carbon nanotubes intertwine on the surface of the lithium oxalate matrix to form a continuous and dense conductive network, constructing a stable and continuous three-phase synergistic structure of "catalytic phase-lithium source phase-conductive phase".
[0027] The preparation steps are as follows: S1. Material mixing: Co3O4, carbon nanotubes and lithium oxalate are dispersed in deionized water at a mass ratio of 2:1:12. After thorough stirring and ultrasonic dispersion, the mixture is dried to obtain the mixture. S2. Dry ball milling: The mixture is placed in a high-energy ball mill with a jacketed water-cooled ball mill jar. The ball milling temperature is controlled at <50℃. Zirconia balls are used as the ball milling medium with a ball-to-material ratio of 15:1. Under argon atmosphere protection (oxygen concentration <1ppm), the speed is set to 500rpm and dry ball milling is carried out for 3 hours to obtain the ball milling product. The energy input is 1.2kWh / kg. S3. Post-processing: The ball-milled product is passed through a 200-mesh sieve, the composite powder is collected, and vacuum dried at 60℃ for 5 hours to obtain the Co3O4 / carbon nanotube composite lithium oxalate supplement.
[0028] Microscopic morphological characterization: Scanning electron microscopy (SEM) was performed on lithium oxalate raw material and Co3O4 / carbon nanotube composite lithium oxalate supplement obtained by ball milling, respectively. The results are as follows: Figure 1 , Figure 2 As shown: From Figure 1 It can be seen that lithium oxalate raw materials are irregularly shaped lumps with a wide size distribution (approximately 10–100 μm), smooth and dense surfaces, and no obvious defects or pores. Their limited specific surface area results in poor intrinsic conductivity and slow decomposition kinetics. Figure 2 It can be seen that the spherical Co3O4 nanoparticles do not show obvious agglomeration, are uniformly dispersed and tightly attached to the surface of the lithium oxalate matrix, and some particles are embedded in the microcracks and pores on the surface of the lithium oxalate particles. The carbon nanotubes are intertwined on the surface of lithium oxalate and interwoven with the Co3O4 nanoparticles to form a continuous and dense conductive network, clearly showing the three-phase synergistic microstructure of "catalytic phase-lithium source phase-conductive phase". This verifies that the dry ball milling composite process can achieve uniform dispersion and tight interfacial coupling of each component, and provides microstructure support for improving the catalytic activity and conductivity of the lithium supplement.
[0029] Battery assembly: The lithium supplementer prepared in this embodiment is added at 8% of the mass of the positive electrode active material NCM811. The positive electrode active material NCM811 containing the lithium supplementer, conductive carbon black (SuperP), and PVDF binder are mixed at a mass ratio of 90:5:5 to form a slurry, which is then coated onto an aluminum foil current collector. After drying and rolling, a positive electrode sheet is obtained. Using a lithium metal sheet as the negative electrode, Celgard 2400 as the separator, and 1 mol / L LiPF6 EC / DEC / EMC (volume ratio 1:1:1) electrolyte (with 1.5% LiODFB added as a film-forming agent) as the electrolyte, coin cell half-cells and full cells are assembled.
[0030] Performance testing: Linear sweep voltammetry (LSV, scan rate 0.1 mV / s) tests showed that the decomposition voltage of this lithium replenisher was 3.78 V, significantly lower than the decomposition potential of pure lithium oxalate (>4.5 V), and highly matched the stability window of commercial electrolytes. Coin cell test results showed that the battery achieved a coulombic efficiency of 94.5% in the first week, a capacity retention rate of 91.2% after 100 cycles, and a capacity decay rate of only 0.088% / week, far superior to the comparative sample without the lithium replenisher. This fully demonstrates the excellent effect of the lithium replenisher in improving the electrochemical performance of the battery in the first week and its long-term cycle stability.
[0031] Example 2: Co3O4 / conductive carbon black composite lithium oxalate supplement This embodiment provides a Co3O4 / conductive carbon black composite lithium oxalate supplement, which is composed of a lithium oxalate matrix, Co3O4, and Ketjenblack EC-600JD conductive carbon black. The lithium oxalate is a commercially available raw material with a purity ≥99.5% and D50=5μm; the Co3O4 is a commercially available raw material with a particle size of 90nm; and the Ketjenblack EC-600JD conductive carbon black is a high specific surface area conductive carbon black. The Co3O4 is uniformly dispersed at the nanoscale and embedded in the microcracks and pores on the surface of the lithium oxalate particles, forming an electronic coupling with the lithium oxalate. Simultaneously, the Co3O4 and Ketjenblack EC-600JD conductive carbon black intertwine on the surface of the lithium oxalate matrix, relying on the high specific surface area carbon black to construct efficient electron transport channels, forming a continuous and dense conductive network, and constructing a stable and continuous three-phase synergistic structure of "catalytic phase-lithium source phase-conductive phase".
[0032] The preparation steps are as follows: S1. Material mixing: Co3O4, KetjenblackEC-600JD and lithium oxalate are dispersed in deionized water at a mass ratio of 2.2:1.2:13. After thorough stirring and ultrasonic dispersion, the mixture is dried to obtain the mixture. S2. Dry ball milling: Add 0.5 wt% of surfactant PVP to the mixture, place the mixture with added PVP in a high-energy ball mill, use a jacketed water-cooled ball mill jar, control the ball milling temperature at <50℃, use zirconia balls as the ball milling medium, and the ball-to-material ratio is 15:1; under nitrogen atmosphere protection (oxygen concentration <1 ppm), set the speed to 450 rpm, and perform dry ball milling for 2 hours to obtain the ball milling product. The energy input is 1.0 kWh / kg. S3. Post-processing: The ball-milled product is passed through a 200-mesh sieve, the composite powder is collected, and vacuum dried at 60℃ for 5.5h to obtain the Co3O4 / conductive carbon black composite lithium oxalate supplement.
[0033] X-ray photoelectron spectroscopy (XPS) characterization: XPS C1s spectra were performed on the Co3O4 / conductive carbon black composite lithium oxalate supplement prepared in this embodiment, and the results are as follows: Figure 3 As shown: The spectrum exhibits a strong characteristic peak at 284.6 eV, corresponding to the sp content in conductive carbon black (Ketjenblack EC-600JD). 2 The hybrid C=C bond, with its sharp peak and no significant shift, indicates that the conjugated conductive structure of the carbon black was not destroyed during the recombination process, ensuring the integrity of the conductive network of the system. The weak characteristic peak at 290–292 eV is consistent with the binding energy of carbon oxalate in the standard spectrum of pure lithium oxalate, corresponding to the signal of C=O and CO bonds in lithium oxalate, verifying the presence of the lithium oxalate component. No new chemical state peaks appeared in the spectrum, and the main peak did not shift significantly, indicating that no significant chemical bonds were formed between carbon black, lithium oxalate, and Co3O4. The interface was mainly physically intertwined, avoiding the destruction of the conductive network caused by strong chemical bonds.
[0034] Battery assembly: The lithium supplement agent prepared in this example was added at 11% of the mass of the positive electrode active material NCM811. The remaining electrode preparation and battery assembly steps were the same as in Example 1.
[0035] Performance testing: Linear sweep voltammetry (LSV, scan rate 0.1 mV / s) tests showed that the decomposition potential of this lithium replenisher was 3.82 V; coin cell test results showed that the coulombic efficiency of the battery reached 91.8% in the first week, the capacity retention rate was 94.2% after 100 cycles, and the capacity decay rate was only 0.105% / week. Relying on the high specific surface area advantage of Ketjenblack EC-600JD, an efficient electron transport channel can be constructed to ensure the catalytic activity and electrochemical kinetic performance of the lithium replenisher; however, the system stability of this structure is slightly lower than that of the carbon nanotube (CNT) system in Example 1.
[0036] Example 3: Co3O4 / graphene composite lithium oxalate supplement This embodiment provides a Co3O4 / graphene composite lithium oxalate supplement, which is composed of a lithium oxalate matrix (commercially available, purity ≥99.5%, D50=5μm), Co3O4 (commercially available, particle size 90nm), and few-layer graphene (sheet thickness ≤5nm, sheet diameter 1~5μm). Co3O4 is uniformly dispersed at the nanoscale and embedded in the microcracks and pores on the surface of lithium oxalate particles, forming an electronic coupling with lithium oxalate. At the same time, Co3O4 and few-layer graphene intertwine on the surface of the lithium oxalate matrix to form a continuous and dense two-dimensional conductive network, constructing a stable and continuous three-phase synergistic structure of "catalytic phase-lithium source phase-conductive phase".
[0037] The preparation steps are as follows: S1. Material mixing: Co3O4, few-layer graphene and lithium oxalate are dispersed in deionized water at a mass ratio of 1.8:0.9:12. After thorough stirring and ultrasonic dispersion, the mixture is dried to obtain the mixture. S2. Dry ball milling: Add 0.5 wt% of surfactant SDS to the mixture, place the mixture with added SDS in a high-energy ball mill, use a jacketed water-cooled ball mill jar, control the ball milling temperature at <50℃, use zirconia balls as the ball milling medium, and the ball-to-material ratio is 15:1; under argon atmosphere protection (oxygen concentration <1 ppm), set the speed to 400 rpm, and perform dry ball milling for 3 hours to obtain the ball milling product. The energy input is 1.5 kWh / kg. S3. Post-processing: The ball-milled product is passed through a 200-mesh sieve, the composite powder is collected, and vacuum dried at 60℃ for 5 hours to obtain the Co3O4 / graphene composite lithium oxalate supplement.
[0038] Battery assembly: The lithium supplement agent prepared in this example was added at 10% of the mass of the positive electrode active material NCM811. The remaining electrode preparation and battery assembly steps were the same as in Example 1.
[0039] Performance testing: Linear sweep voltammetry (LSV, scan rate 0.1 mV / s) tests showed that the decomposition potential of this lithium replenisher was 3.81 V; coin cell test results showed that the coulombic efficiency of the battery reached 92.7% in the first cycle, the capacity retention rate was 95.1% after 100 cycles, and the capacity decay rate was only 0.133% / week. Relying on the two-dimensional conductive network constructed by few-layer graphene, the interfacial electron migration ability was significantly improved, further ensuring the catalytic activity and electrochemical kinetic performance of the lithium replenisher.
[0040] Example 4: Mn3O4 / carbon nanotube composite lithium oxalate supplement This embodiment provides a Mn3O4 / carbon nanotube composite lithium oxalate supplement, which is composed of a lithium oxalate matrix, Mn3O4, and carbon nanotubes (CNTs). The lithium oxalate is a commercially available raw material with a purity ≥99.5% and a D50 of 5μm. The Mn3O4 is commercially available manganese tetroxide nanoparticles with a particle size of 80nm. The carbon nanotubes have a diameter of 20nm and a length of 1–5μm. The Mn3O4 is uniformly dispersed at the nanoscale and embedded in the microcracks and pores on the surface of the lithium oxalate particles, forming an electronic coupling with the lithium oxalate. Simultaneously, Mn3O4 and carbon nanotubes intertwine on the surface of the lithium oxalate matrix, forming a continuous and dense conductive network, thus constructing a stable and continuous three-phase synergistic structure of "catalytic phase-lithium source phase-conductive phase".
[0041] The preparation steps are as follows: S1. Material mixing: Mn3O4, carbon nanotubes (CNTs) and lithium oxalate are dispersed in deionized water at a mass ratio of 1.5:1.0:13. After thorough stirring and ultrasonic dispersion, the mixture is dried to obtain the mixture. S2. Dry ball milling: The mixture is placed in a high-energy ball mill with tungsten carbide balls as the milling medium at a ball-to-material ratio of 10:1. Under an argon atmosphere (oxygen concentration <1ppm), the rotation speed is set to 480rpm, and a pulse operation strategy is adopted (10min operation followed by 5min intermittent operation). The ball milling temperature is controlled at <50℃, and dry ball milling is carried out for 3 hours (2 hours of operation followed by 1 hour intermittent operation) to obtain the ball milled product. The energy input is 1.3kWh / kg. S3. Post-processing: The ball-milled product is passed through a 300-mesh sieve, the composite powder is collected, and vacuum dried at 60℃ for 5.5h to obtain Mn3O4 / carbon nanotube composite lithium oxalate supplement.
[0042] Microscopic morphological characterization: The Mn3O4 / carbon nanotube composite lithium oxalate supplement prepared in this embodiment was tested by scanning electron microscopy (SEM), and the results are as follows: Figure 4 As shown, Mn3O4 nanoparticles are uniformly dispersed and tightly attached to the surface of the lithium oxalate matrix, with some particles embedded in the microcracks and pores of the matrix surface. Carbon nanotubes are intertwined and interwoven on the matrix surface, forming a continuous and dense three-dimensional conductive network together with the Mn3O4 nanoparticles. This clearly presents a three-phase synergistic microstructure of "catalytic phase-lithium source phase-conductive phase", which verifies that the dry ball milling composite process can achieve uniform dispersion and interfacial coupling of each component, providing structural support for improving the catalytic activity and conductivity of the lithium supplement.
[0043] Battery assembly: Add the lithium supplement agent prepared in this example at 9% of the mass of the positive electrode active material NCM811. The remaining electrode preparation and battery assembly steps are the same as in Example 1.
[0044] Performance testing: Linear sweep voltammetry (LSV, scan rate 0.1 mV / s) tests showed that the decomposition potential of this lithium replenisher was 3.74 V. Coin cell testing results showed that the coulombic efficiency reached 91.5% in the first cycle, and the capacity retention rate was 94.7% after 100 cycles, with a capacity decay rate of only 0.092% / cycle. The redox activity of Mn3O4 combined with the highly efficient conductive network of carbon nanotubes further enhanced the lithium release capacity and electrochemical kinetics performance of the lithium replenisher.
[0045] Example 5: Fe3O4 / carbon nanotube composite lithium oxalate supplement This embodiment provides a Fe3O4 / carbon nanotube composite lithium oxalate supplement, which is composed of a lithium oxalate matrix, Fe3O4, and carbon nanotubes (CNTs). The lithium oxalate is a commercially available raw material with a purity ≥99.5% and a D50 of 5μm. The Fe3O4 is commercially available iron tetroxide nanoparticles with a particle size of 120nm. The carbon nanotubes have a diameter of 20nm and a length of 1–5μm. The Fe3O4 is uniformly dispersed at the nanoscale and embedded in the microcracks and pores on the surface of the lithium oxalate particles, forming an electronic coupling with the lithium oxalate. Simultaneously, Fe3O4 and carbon nanotubes intertwine on the surface of the lithium oxalate matrix, forming a continuous and dense conductive network, constructing a stable and continuous three-phase synergistic structure of "catalytic phase-lithium source phase-conductive phase".
[0046] The preparation steps are as follows: S1. Material mixing: Fe3O4, carbon nanotubes (CNTs) and lithium oxalate are mixed at a mass ratio of 1.5:0.8:12. After thorough stirring, ultrasonic dispersion and drying, a mixture is obtained. S2. Dry ball milling: The mixture is placed in a high-energy ball mill with a jacketed water-cooled ball mill jar. The ball milling temperature is controlled at <50℃. Zirconia balls are used as the ball milling medium with a ball-to-material ratio of 20:1. Under nitrogen atmosphere protection (oxygen concentration <1ppm), the speed is set to 450rpm and dry ball milling is carried out for 2 hours to obtain the ball milling product. The energy input is 1.0kWh / kg. S3. Post-processing: The ball-milled product is passed through a 220-mesh sieve, the composite powder is collected, and vacuum dried at 50℃ for 6 hours to obtain Fe3O4 / carbon nanotube composite lithium oxalate supplement.
[0047] Battery assembly: The lithium supplement agent prepared in this example was added at 8% of the mass of the positive electrode active material NCM811. The remaining electrode preparation and battery assembly steps were the same as in Example 1.
[0048] Performance testing: Linear sweep voltammetry (LSV, scan rate 0.1 mV / s) tests showed that the decomposition potential of this lithium supplement was 3.76 V. Coin cell testing results showed that the coulombic efficiency reached 92.0% in the first cycle, and the capacity retention rate was 95.6% after 100 cycles, with a capacity decay rate of only 0.148% / cycle. The strong magnetic and electron affinity of Fe3O4 helps to stably disperse the active components during ball milling, further ensuring the catalytic activity and electrochemical kinetic performance of the lithium supplement.
[0049] Comparative Example 1: Preparation of CO3O4 / carbon nanotube composite lithium oxalate supplement by wet process This comparative example provides a CO3O4 / carbon nanotube composite lithium oxalate supplement prepared by a wet process. The same raw materials as in Example 1 are selected, mixed at a mass ratio of 2:1:12, wet dispersed in ethanol, freeze-dried, and then processed under the ball milling conditions of Example 1. The total energy consumption of the process is 5.2 kWh / kg.
[0050] Microscopic morphological characterization: The CO3O4 / carbon nanotube composite lithium oxalate supplement prepared by this comparative wet process was tested by scanning electron microscopy (SEM), and the results are as follows: Figure 5 As shown: It can be seen that the lithium supplement particles are significantly agglomerated. The CO3O4 nanoparticles and carbon nanotubes are unevenly distributed on the surface of the lithium oxalate matrix, forming large agglomerates in some areas. The three-phase synergistic structure is destroyed, the interfacial coupling degree is significantly reduced, and a continuous and dense conductive network cannot be formed, resulting in a significant weakening of the synergistic effect of catalysis and conductivity.
[0051] Battery assembly: Same as in Example 1.
[0052] Performance testing: Linear sweep voltammetry (LSV, scan rate 0.1 mV / s) tests showed that the decomposition potential of the lithium replenisher was 3.84 V. Coin cell testing results showed that the coulombic efficiency in the first week was 89.5%, significantly lower than the product prepared by dry ball milling in Example 1. This is mainly attributed to the material agglomeration and insufficient interfacial coupling caused by the wet dispersion-freeze-drying process, which weakened the synergistic effect between the catalytic and conductive phases. Simultaneously, the total energy consumption of the process (5.2 kWh / kg) was much higher than the 1.2 kWh / kg of Example 1, demonstrating the dual advantages of the dry ball milling process in terms of both performance and energy consumption.
[0053] Comparative Example 2: Catalyst-free pure lithium oxalate lithium supplement This comparative example directly uses commercial lithium oxalate (purity ≥99.5%, particle size 3-8μm) as a lithium supplement, without adding any transition metal oxide catalysts or conductive carbon materials.
[0054] Battery assembly: Same as in Example 1.
[0055] Performance testing: Linear sweep voltammetry (LSV, scan rate 0.1 mV / s) tests showed that the decomposition potential of this pure lithium oxalate supplement was as high as 4.52 V, exceeding the stability window of conventional electrolytes; coin cell tests showed that the coulombic efficiency in the first week was only 83.2%, and the capacity decay rate after 100 cycles was >0.5% / week. Due to the lack of a synergistic structure between the catalytic and conductive phases, there is no effective catalytic center or continuous conductive pathway, resulting in difficult decomposition of lithium oxalate, low lithium release efficiency, and extremely poor lithium supplementation effect.
[0056] The test results from the above embodiments and comparative examples show that: This invention utilizes a three-phase synergistic structure of "catalytic phase-lithium source phase-conductive phase" constructed through a dry ball milling process. This structure can significantly reduce the decomposition potential of lithium oxalate from 4.52V for pure lithium oxalate to 3.74–3.82V, which is highly compatible with the stability window of commercial electrolytes. Simultaneously, it improves the coulombic efficiency of the battery in the first cycle to 91.5%–94.5%, and controls the capacity decay rate after 100 cycles to 0.088%–0.15% / week, which is far superior to the lithium replenishment effect of pure lithium oxalate.
[0057] Compared with the wet process of Comparative Example 1, the dry ball milling process of the present invention ensures uniform dispersion of components and sufficient interfacial coupling, while the total energy consumption of the process is only 1.0 to 1.5 kWh / kg, which is much lower than the 5.2 kWh / kg of the wet process, achieving the dual advantages of improved performance and reduced energy consumption.
[0058] Combinations of different transition metal oxides (CO3O4, Mn3O4, Fe3O4) with highly conductive carbon materials (carbon nanotubes, conductive carbon black, graphene) can all effectively improve lithium replenishment performance. Among them, the CO3O4 / carbon nanotube system performs best, with a first-cycle coulombic efficiency of 94.5% and the best cycle stability. Different carbon materials have their own strengths: carbon nanotubes are better in structural stability, graphene is more outstanding in electron migration ability, and conductive carbon black has more advantages in cost and process compatibility.
[0059] When the amount of lithium supplementer added is 8% to 12% of the mass of the positive electrode active material, the best balance between lithium source compensation and catalytic effect can be achieved without diluting the effective capacity of the positive electrode or significantly increasing the electrode thickness and interfacial impedance. This avoids problems such as limited lithium supplementation effect due to insufficient addition or side reactions and electrode expansion due to excessive addition.
[0060] In summary, the transition metal oxide composite lithium oxalate supplement provided by this invention significantly improves the first-cycle coulombic efficiency and long-cycle stability of lithium-ion batteries through a three-phase synergistic structure design and dry ball milling process. It also has advantages such as simple process, low energy consumption, and good compatibility. Moreover, the raw materials are all commercially available conventional products with high batch stability and broad prospects for industrial application.
[0061] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit them; those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions will not cause the essence of the corresponding technical solutions to deviate from the protection scope of the present invention.
Claims
1. A method for preparing a transition metal oxide composite lithium oxalate lithium supplement, characterized in that, Includes the following steps: S1. Material Mixing: Transition metal oxides, highly conductive carbon materials, and lithium oxalate are mixed in a mass ratio of (1.5–2.5):(0.8–1.5):(12–15) to obtain a mixture; the transition metal oxide is at least one of Mn3O4, Fe3O4, and Co3O4; the highly conductive carbon material is at least one of carbon nanotubes, few-layer graphene, and conductive carbon black. S2. Dry ball milling composite: The mixture is placed in a high-energy ball mill, with zirconium oxide or tungsten carbide as the ball milling medium. Under an inert atmosphere, the ball-to-material ratio is set to 10:1 to 20:1, the rotation speed is 400 to 500 rpm, the ball milling time is 2 to 3 hours, and the energy input is 1.0 to 1.5 kWh / kg for dry ball milling composite. This allows the transition metal oxides and highly conductive carbon materials to be uniformly dispersed and embedded in the lithium oxalate matrix to form an electronic coupling interface. S3. Post-processing: After the ball-milled product is passed through a 200-300 mesh sieve, the composite powder is collected and vacuum dried to obtain the transition metal oxide composite lithium oxalate supplement.
2. The preparation method according to claim 1, characterized in that: The transition metal oxide in step S1 has a particle size of 50–150 nm; the lithium oxalate has a purity of ≥99.5% and a particle size of 3–8 μm.
3. The preparation method according to claim 1, characterized in that: The conductive carbon black mentioned in step S1 is Super P or Ketjenblack EC-600JD.
4. The preparation method according to claim 1, characterized in that: The inert atmosphere in step S2 is argon or nitrogen, and the oxygen concentration in the inert atmosphere is <1 ppm.
5. The preparation method according to claim 1, characterized in that: Before the dry ball milling compounding in step S2, 0.5 wt% of a surfactant, namely PVP or SDS, is added to the mixture.
6. The preparation method according to claim 1, characterized in that: The dry ball milling process described in step S2 employs a jacketed water-cooled ball mill jar or a pulse operation strategy to control the ball milling temperature at <50℃.
7. The lithium supplement agent for transition metal oxide composite lithium oxalate prepared by the preparation method according to any one of claims 1-6, characterized in that: The transition metal oxide is uniformly dispersed at the nanoscale and embedded in the microcracks and pores on the surface of lithium oxalate particles, forming an electronic coupling with lithium oxalate. Furthermore, the transition metal oxide and highly conductive carbon material intertwine on the surface of the lithium oxalate matrix to form a continuous conductive network, constructing a continuous three-phase synergistic structure of "catalytic phase-lithium source phase-conductive phase".
8. The application of the transition metal oxide composite lithium oxalate supplement agent according to claim 7 as a positive electrode additive for lithium-ion batteries in the preparation of positive electrode sheets for lithium-ion batteries.
9. The application according to claim 8, characterized in that: The amount of the transition metal oxide composite lithium oxalate supplement agent added to the positive electrode of the lithium-ion battery is 8-12% of the mass of the positive electrode active material.